2022
DOI: 10.1038/s41598-022-11829-x
|View full text |Cite
|
Sign up to set email alerts
|

BRG1 is a biomarker of hypertrophic cardiomyopathy in human heart specimens

Abstract: Hypertrophic cardiomyopathy (HCM) is a genetic disease of the sarcomere that causes otherwise unexplained cardiac hypertrophy and is associated with sudden death. While previous studies showed the role of the epigenetic modifier Brg1 in mouse models of HCM, additional work is needed to identify its role in humans. We tested the hypothesis that BRG1 expression is increased in periods of cardiac remodeling during fetal growth and in development of HCM. We employed immunohistochemical staining to evaluate protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Immunohistochemical staining from 796 human cardiac specimens found that Brg1 expression significantly increased in patients with HCM compared to other causes of ventricular hypertrophy and dilated cardiomyopathy (DCM). In vitro, inhibition of Brg1 significantly decreased cardiomyocyte β-MHC expression and increased α- MHC expression ( 73 ), consistent with findings reported by Hang et al ( 72 ). However, the evidence of Brg1 as the causative gene for HCM is remained limited.…”
Section: Role Of Sfⅱ Helicases In the Cardiomyopathiessupporting
confidence: 89%
See 1 more Smart Citation
“…Immunohistochemical staining from 796 human cardiac specimens found that Brg1 expression significantly increased in patients with HCM compared to other causes of ventricular hypertrophy and dilated cardiomyopathy (DCM). In vitro, inhibition of Brg1 significantly decreased cardiomyocyte β-MHC expression and increased α- MHC expression ( 73 ), consistent with findings reported by Hang et al ( 72 ). However, the evidence of Brg1 as the causative gene for HCM is remained limited.…”
Section: Role Of Sfⅱ Helicases In the Cardiomyopathiessupporting
confidence: 89%
“…However, the reactivation of fetal genes may induce cardiac pathologic hypertrophy ( 72 ). Moreover, Brg1 has been reported to be associated with hypertrophic cardiomyopathy (HCM) and heart failure (HF) pathological remodeling mechanisms ( 73 , 74 ). Brg1 reactivated in the adult myocardium, in this setting, may promote pathology and adverse remodeling rather than the regenerative response.…”
Section: Role Of Sfⅱ Helicases In MI and Ischemia/reperfusion Injury ...mentioning
confidence: 99%
“…BRG1 ( Smarca4 ) is silenced in adult cardiac myocytes, but reactivated by cardiac stresses such as increased afterload resulting from TAC (transverse aortic constriction) or hypertension 54 , leading to the formation of SWI/SNF complexes that remodel chromatin, activate the fetal cardiac gene program 54 and promote cardiac remodeling. An immunohistochemical study of BRG1 expression in human heart tissue revealed higher BRG1 expression in HCM than DCM, and other causes of LVH 55 . Our regulon analysis predicted Smarca4 regulon activation in mutant ventricular cardiomyocytes but not in control cardiomyoctes ( Fig 2h ).…”
Section: Discussionmentioning
confidence: 97%
“…An immunohistochemical study of BRG1 expression in human heart tissue revealed higher BRG1 expression in HCM than DCM, and other causes of LVH 55 . Our regulon analysis predicted Smarca4 regulon activation in mutant ventricular cardiomyocytes but not in control cardiomyoctes (Fig 2h).…”
Section: Myocyte Hypertrophymentioning
confidence: 97%
“…BRG1 is part of the SWI/SNF complex, with ATPase and helicase activity, that participates in chromatin remodeling. Although the underlying pathway related to BRG1 is not yet fully elucidated, a recent human in vitro study demonstrated that BRG1 is highly expressed in hypertrophic cardiomyopathy and can alter myosin expression [ 54 ]. The rs9349379 SNP in the PHACTR1 gene is an eQTL that has been found to be associated with CAD risk.…”
Section: Discussionmentioning
confidence: 99%